Associations of chronic hepatitis C with metabolic and cardiac outcomes. Issue 6 (5th February 2013) - Younossi, Z. M.; Stepanova, M.; Nader, F.; Younossi, Z.; Elsheikh, E.
Summary Background Chronic hepatitis C virus (CH‐C) infection is associated with metabolic conditions such as insulin resistance and type 2 diabetes (DM) and may increase the risk of cardiovascular diseases. Aim To assess the association of CH‐C with risk factors for cardiovascular diseases using US population data. Methods The National Health and Nutrition Examination Surveys (NHANES) collected between 1999 and 2010 were used. Results Of 19 741 participants considered eligible for the study. Of this cohort, 173 individuals (0.88%) had detectable HCV RNA and were considered to have CH‐C. Compared with controls, CH‐C patients were predominantly African American (23.5% vs. 10.5%, P < 0.0001), men (66.6% vs. 46.1%, P = 0.0001), more likely to be between 45 and 55 years of age (41.9% vs. 20.4%, P = 0.0001), had higher rate of insulin resistance (44.1% vs. 31.1%, P = 0.0301), hypertension (40.1% vs. 28.9%, P = 0.0201), and history of smoking (76.2% vs. 29.9%, P < 0.0001). In multivariate analysis, in addition to known risk factors for insulin resistance, CH‐C was independently associated with the presence of insulin resistance [OR (95% CI) = 2.06 (1.19–3.57)], DM [OR = 2.31 (1.18–4.54)] and hypertension [OR = 2.06 (1.30–3.24)]. Independent predictors of cardiovascular diseases included older age, presence of obesity and smoking. CH‐C was independently associated with congestive heart failure subtype of cardiovascular diseases but not ischaemic heart disease and stroke. Conclusion Chronic hepatitis C virus infection is independently associated with presence of metabolic conditions (insulin resistance, type 2 diabetes mellitus and hypertension) and congestive heart failure.